Swimming Impedes Intestinal Microbiota and Lipid Metabolites of Tumorigenesis in Colitis-Associated Cancer - Weiyi Wang; Ying Xu; Xiaofeng Wang; Yimin Chu; Haiqin Zhang; Lu Zhou; Haijin Zhu; Ji Li; Rong Kuai; Fengli Zhou; Daming Yang; Haixia Peng (Frontiers in Oncology, 2022)
BackgroundAccumulating data support that regular physical activity potentially inhibits chronic colitis, a risk factor for colitis-associated cancer (CAC). However, possible effects of physical activity on CAC and the underlying mechanisms remain poorly understood.MethodsA pretreatment of swimming on azoxymethane/dextran sodium sulfate (AOM/DSS)-induced CAC mice was implemented to determine its protective effect. Inflammation and tumorigenesis were assessed using colorectums from C57BL/6 mice. In order to determine how swimming alters colonic lipid metabolism and gene expression, a comparative analysis was conducted. Meanwhile, alterations in intestinal microbiota and short-chain fatty acids (SCFAs) were detected and analyzed. Finally, an integration analysis of colonic lipid metabolism with gene expression and intestinal microbiota was performed respectively.ResultSwimming pretreatment relieved bowel inflammation and minimized tumor formation. We demonstrated that prostaglandin E2 (PGE2)/PGE2 receptor 2 subtype (EP2) signaling as a potential regulatory target for swimming induces colonic lipid metabolites. Swimming-induced genera, Erysipelatoclostridium, Parabacteroides, Bacteroides, and Rikenellaceae_RC9_gut_group, induced intestinal SCFAs and affected the function of colonic lipid metabolites enriched in glycerophospholipid metabolism and choline metabolism in cancer.ConclusionAccording to our experiments, swimming pretreatment can protect mice from CAC by intervention in the possible link between colonic lipid metabolites and PGE2/EP2 signaling. Further, swimming-induced genera and probiotics promoted glycerophospholipid metabolism and choline metabolism in cancer, the major constituents of colonic lipid metabolites, and increased SCFAs, which were also important mechanisms for the anti-inflammatory and anti-tumorigenic effects of swimming.